In Memory of Professor Bogdan Bojarski (Український математичний вісник, 2018)
Editorial Board of the Ukrainian Mathematical Bulletin was deeply saddened to learn of the passing away on 22 December, 2018 of Bogdan Tadeusz Bojarski, one of the greatest mathematicians of his generation, a brilliant scientist and remarkable personality, a permanent member of the International Editorial Board of our journal